Case–Control Study of Inflammatory Mediators in Psoriasis and its Correlation with the Psoriasis Area and Severity Index - Jeevith Chandrashekara Reddy; Y Hari Kishan Kumar (Clinical Dermatology Review)
Background: Acute-phase reactants (APRs) in psoriasis are especially released under the influence from the liver of interleukin (IL)-6 that include serum amyloid A, ceruloplasmin, ferritin, complements, haptoglobin, fibrinogen, C-reactive protein, and erythrocyte sedimentation rate (ESR). IL-23, IL-17, IL-12, interferon-γ, and tumor necrosis factor (TNF)-α are corresponding cytokines that could be included. We conducted this research to assess the serum levels of inflammatory mediators such as TNF-α, IL-17, IL-12, IL-23, CRP, and ESR in patients having psoriasis and also to correlate them with the “Psoriasis Area and Severity Index” (PASI) and to compare with normal healthy controls. Settings and Design: This was a case–control analysis with 100 participants, 50 cases of psoriasis, and 50 nonpsoriatic patients. Patients were evaluated for immunological mediators such as CRP, ESR, and TNF-α, IL-12, IL-17, and IL-23 ELISA KIT (R and D systems), and also punch biopsy and dermoscopy were done. PASI, a worksheet of the British Association of Dermatologists, assessed the severity of the disease clinically. Results: As this study was age- and gender-matched, the age distribution and gender distribution among cases and controls were the same. The average serum concentrations of TNF-α, IL-12, IL-17, IL-23, CRP, and ESR were substantially greater in psoriatic patients compared to controls (t-test; P <0.001). There were significant relationships observed between the PASI and cytokine serum levels (rank test of Spearman; P <0.001). Conclusions: Further large-scale clinical studies on inflammatory markers in psoriasis are suggested to determine its precise role during the illness pathogenesis and also in their treatment and prognosis.